Factors Affecting Investment Decisions of Students on Nepal Stock Exchange: Evidence from Constituent Colleges of Pokhara University - Khadka, Sumina; Dhakal, Sunil (Journal of Business and Management, 2025)
Background: The stock market demands raising funds for businesses and individual investors, especially with respect to flexibility and transaction efficiency. Understanding investor behavior and factors influencing investment decisions matters when current information facilitates stock market transactions. Finding knowledge gaps in investments and investigating the driving forces behind students’ decisions can enhance financial literacy and guide the development of regulations. Objectives: The study examines the behavioral and psychological factors, demographic and personal attributes, market and economic traits, and financial and quantitative variables influencing students’ investment decisions in Nepal, with a specific focus on Nepal Stock Exchange. Materials and Methods: The research has used both descriptive and causal research methods to explore factors influencing students’ investment decisions in the Nepal Stock Exchange. Data was collected through a structured questionnaire from a sample of 248 students enrolled at Pokhara University constituent colleges, using convenience and purposive sampling techniques. Descriptive and inferential statistical methods were used to analyze the data, providing insights into current investment behaviors and the underlying causes of decision-making. Results: The results have shown that financial and quantitative variables have the strongest influence on students’ investment decisions. Demographic and personal attributes and market and economic variables also have a significant effect. In contrast, behavioral and psychological factors were not found to have a significant impact on investment decisions. Conclusion: Demographic factors, financial literacy, and market knowledge significantly influence investment decisions among university students. It further suggests that particular financial education, workshops, and improved market information can enhance their skills.